Artificial intelligence in space - Singer, Anže (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2024)
European Space Agency was established on 30 October 1980. It currently has twenty- three Member States, and its mission is to shape the development of the European space capability and to ensure that investment in space is continued in the direction of bringing benefits to European citizens and the world. Artificial intelligence (AI) can be seen as intelligence exhibited by machines that can observe, perceive and act upon their environment to maximise their chance of success at a given goal. AI can be an important and enabling technology for space missions, bringing added value for scientific return and for the efficiency of the mission itself. The most successful AI implementations are still rarely used in the space industry today, as the models developed within the neural network are not human-readable. Despite the challenges, there are examples where AI is successfully being demonstrated in the space sector through ESA’s own activities. The fast-evolving field of space research and technology, AI, and the related applications are raising numerous doubts and debates while challenging the adequacy of traditional space law. There is a looming concern as to whether the legal framework is up to date to meet the challenges that may arise within the AI and space sector, and what can be done to meet those challenges accordingly and on time. Others also argue that, in addition to liability concerns, ensuring confidentiality and data protection are some of the more acute issues in the context of AI.